The moderating effect of match external load on neuromuscular performance in U-18 English Premier League academy football players: A principal component regression approach - Springham, M.; Singh, N.; Stewart, P.; Matthews, J.; Jones, I.; Norton-Sherwood, C.; May, D.; Salter, J.; Strudwick, A. J.; Shaw, J. W. (The Journal of Strength and Conditioning Research, 2025)
We examined the moderating effect of match external load measures on neuromuscular performance in U-18 English Premier League (EPL) football players. Seventeen male outfield players completed countermovement jump (CMJ) and isometric hip adductor (IADS) and posterior chain strength tests 1 day before (MD-1) and 2 days after (MD+2) 8 competitive games. Total, high-speed running, high metabolic load, explosive and Zone6 distances, and the total number of accelerations and decelerations were recorded using global positioning system and microelectrical mechanical sensor devices. Standardized changes to neuromuscular performance measures (CMJ jump height and IADS and isometric posterior chain strength peak force) were summated to create a total score of neuromuscular performance. Principal component (PC) analysis and a linear mixed-effects regression model examined the relationships between external load and neuromuscular performance changes with significance set to p < 0.050. Two PCs explained 93% of the variance in external load variables. PC1 had an equal contribution from all external load metrics and was therefore considered representative of total match volume. PC2 was primarily composed from Zone6 and high-speed running distance and was therefore considered representative of high-speed running and sprint volume. Standardized neuromuscular performance reduced by 0.85 from MD-1 to MD+2. PC1 (mean: 0.0 ± 2.4, range: -5.9 to 4.8) had a significant negative relationship with neuromuscular performance (ß = -0.23, p = 0.044) and IADS peak force (ß = -0.15, p = 0.007), but no other components exerted significant effects (p = 0.121). Match volume exerts a negative linear effect on neuromuscular performance and IADS peak force in U-18 EPL academy football players.